2011
DOI: 10.1007/s10278-011-9417-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Texture for Classification of Abdominal Aortic Aneurysm After Endovascular Repair

Abstract: The use of the endovascular prostheses in abdominal aortic aneurysm has proven to be an effective technique to reduce the pressure and rupture risk of aneurysm. Nevertheless, in a long-term perspective, complications such as leaks inside the aneurysm sac (endoleaks) could appear causing a pressure elevation and increasing the danger of rupture consequently. At present, computed tomographic angiography (CTA) is the most common examination for medical surveillance. However, endoleak complications cannot always b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 28 publications
(26 reference statements)
0
23
0
1
Order By: Relevance
“…In terms of low-contrast resolution, most previous studies have reported unanimous results that an increase in the percentage of ASIR resulted in increased low-contrast resolution, which is consistent with our results. 2 , 5 , 7 , 10 The CNR was calculated from the HU difference between the cavity and the background divided by the noise value. As noise decreases in proportion to the blending percentage of ASIR without changing the HU of both the cavity and the background, the CNR could only increase.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In terms of low-contrast resolution, most previous studies have reported unanimous results that an increase in the percentage of ASIR resulted in increased low-contrast resolution, which is consistent with our results. 2 , 5 , 7 , 10 The CNR was calculated from the HU difference between the cavity and the background divided by the noise value. As noise decreases in proportion to the blending percentage of ASIR without changing the HU of both the cavity and the background, the CNR could only increase.…”
Section: Discussionmentioning
confidence: 99%
“…This result was similar to that of a previous study which compared the noise spectrum curve of FBP and ASIR images in a water phantom and showed that applying 40% ASIR was considered optimal when the radiation dose is reduced to 50%. 5 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The GLCM is able to identify subtle local variation of pixel intensities, which is necessary to capture altered texture characteristics for classification of burn tissues using ultrasound images. Both the GLCM and GLRLM are shown to have comparable accuracy in classification of optical images [31][32][33] . In this work, GLCM is used for burn classification.…”
mentioning
confidence: 97%